PENGARUH PEMANFAATAN KULIT UBI JALAR UNGU (Ipomoea batatas L.) TERFERMENTASI DALAM RANSUM TERHADAP KARKAS DAN LEMAK ABDOMINAL ITIK BALI - I G., Artadana; Yadnya, T. G. B.; Dewantari, M. (Jurnal Peternakan Tropika, 2016)
The study aims to find out of the effect of the utilization of fermented purple sweet potato ( Ipomoea batatas L.) skin with Aspergillus niger in the diets on carcass and abdominal fat of bali duck have age 22 weeks. This study has been conducted in the Guwang village, subdistrict of Sukawati, Gianyar for 10 weeks. This study was conducted by completely randomized design (CRD) with five treatments and three replications. Each replications contained five bali ducks have age of 12 weeks with mean of weight approximate 866.6 ± 67.06 gram. The five treatments were A : diets without purple sweet potato skin as control ; B : diets containing 10% unfermented purple sweet potato skin ; C : diets containing 10% fermented purple sweet potato skin ; D : diets containing 20% unfermented purple sweet potato skin and E : diets containing 20% fermented purple sweet potato skin. Observed variables consisted are weight, carcass weight, carcass persentage, and abdominal fat (intestine fat, abdominal fat, and gizzard fat). The results showed that the utilization of feed stuffs containing 10% and 20% fermented of purple sweet potato ( Ipomoea batatas L.) skin can improvement weight, carcass weight, and carcass percentage, but statistically not different significant (P>0,05), but it can reduce abdominal fat percentage (intestine fat, abdominal fat, and gizzard fat) significantly (P<0,05) if compared with the control (A). Based on the results of this study concluded that the diets containing 10% and 20% fermented of purple sweet potato ( Ipomoea batatas L.) skin in the diets had not effect on improvement weight, carcass weight, carcass percentage, but have the effect on decrease in the amount of abdominal fat in bali ducks aged 22  weeks.
Keywords: bali duck, purple sweet potato bark, Aspergillus niger, carcass, abdominal fat